2016
DOI: 10.2147/oajc.s97013
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive options for women with premenstrual dysphoric disorder: current insights and a narrative review

Abstract: Premenstrual syndrome and its most severe form, premenstrual dysphoric disorder (PMDD), are two well-defined clinical entities that affect a considerable number of women. Progesterone metabolites and certain neurotransmitters, such as gamma-aminobutyric acid and serotonin, are involved in the etiology of this condition. Until recently, the only treatment for women with PMDD was psychoactive drugs, such as selective serotonin reuptake inhibitors. Several years ago, there has been evidence of the beneficial role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 54 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…However, it is important to keep in mind that although these studies established an association between the use of OCPs and depression, it is unclear whether depressive symptoms were assessed during or after the luteal phase of the menstrual cycle to distinguish whether it was premenstrual syndrome-related depression or generalized depression [ 31 ]. In fact, women suffering from PMS-related depression and PMDD have reported dramatic relief from their symptoms once their menstrual flow begins [ 17 ]. Although our study established a relationship between OCP use and the experience of PMS, it has been reported that OCPs (used to suppress ovulation and regulate the menstrual cycle) could be used in the treatment of PMS, although the results from these studies have been mixed with low quality of evidence[ 16 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to keep in mind that although these studies established an association between the use of OCPs and depression, it is unclear whether depressive symptoms were assessed during or after the luteal phase of the menstrual cycle to distinguish whether it was premenstrual syndrome-related depression or generalized depression [ 31 ]. In fact, women suffering from PMS-related depression and PMDD have reported dramatic relief from their symptoms once their menstrual flow begins [ 17 ]. Although our study established a relationship between OCP use and the experience of PMS, it has been reported that OCPs (used to suppress ovulation and regulate the menstrual cycle) could be used in the treatment of PMS, although the results from these studies have been mixed with low quality of evidence[ 16 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of OCPs containing a combination of an estrogen and progestogen is to suppress ovulation by modifying the natural fluctuation of these hormones [ 14 - 16 ] thereby preventing pregnancy. Although the etiology of PMS remains unclear, it has been suggested that genetic, environmental, and psychological factors contribute to increased sensitivity to normal hormonal changes and neurotransmitter abnormalities which lead to PMS [ 15 , 17 ]. The relationship between OCPs and the development of symptoms of PMS (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, estrogen therapy is used to treat post-partum depression ( Moses-Kolko et al, 2009 ), as well as mood symptoms during menopause ( Toffol et al, 2015 ). Furthermore, oral contraceptives containing the potent estrogen ethinyl-estradiol are used in the treatment of pre-menstrual dysphoric symptoms (for review see Lete and Lapuente, 2016 ). These effects may be mediated via ER-dependent hippocampal actions, since bilateral injection of 17β-estradiol into the dorsal hippocampus has been shown to be anxiolytic ( Walf and Frye, 2006 ; Walf et al, 2006 ; Frye and Rhodes, 2002 ).…”
Section: Effects Of Sex Steroids On the Hippocampus – Behavioral Implmentioning
confidence: 99%
“…Further pharmacological treatments include medications that address the body’s hormonal activity, i.e. oral contraceptives [11] or gonadotropin-releasing hormone agonists [12]. However, the medication used is often associated with substantial side effects, such as nausea, asthenia, and headache [13].…”
Section: Introductionmentioning
confidence: 99%